Efektivitas Pengembangan Modul Fisika Berbasis Problem Based Learning untuk Meningkatkan Penguasaan Konsep Pada Materi Getaran Harmonis - Elza Ulfani; Susilawati Susilawati; I Wayan Gunada (Kappa Journal, 2022)
The research has been carried out on the effectiveness of the development of physics modules based on problem-based learning to improve mastery of concepts in the material of harmonic vibrations. This study aims to produce a product in the form of an effective problem-based learning physics module to improve students' mastery of concepts in harmonic vibration material. This research is a type of research development or Research and Development (R&D) using the ADDIE model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. This article only discussed the implementation stage. The research instrument used is a concept mastery test instrument which is arranged according to the concept mastery indicators, namely C1 to C6 which consists of remembering (C1), understanding (C2), applying (C3), analyzing (C4), evaluating (C5) and creating (C4). C6). Data collection techniques used a pretest at the beginning of learning and a posttest at the end of learning. The effectiveness of the module was analyzed by the N-gain test. Based on the results of the analysis of the pretest and post-test scores, an average N-gain value of 0.67 was obtained in the medium category, it can be concluded that the problem-based learning-based physics module is effective for improving students' mastery of concepts in harmonic vibration material.